Optimal Bid Strategies in Crowdsourcing Contest Based on Multi-Attribute Auctions - Xu, Qi; Zhang, Huixian (International Journal of Emerging Trends in Social Sciences, 2018)
As a business model under the emerging social interaction behavior, crowdsourcing gather public knowledge, skills, and information to help companies directly face consumers, fully explore innovative product design and sales markets, and make full use of Internet advantages to respond market demand. This paper explores crowdsourcing contest which is under a fixed bonus mechanism. The purpose of crowdsourcing is to maximize the sum of bid submitted by contestant. First, we establish utility function both the contestant and the Crowdsourcing and then the optimal solutions to Stackelberg game and then analysis results show that: The increase in the number of contestants will increase the effort for the contest and then decrease; the lower the cost parameter of the contestants, the higher the expected utility; due to the limited ability of contestants, bonuses can’t infinitely motivated contestants, so as the bonus increases, crowdsourcing crowdsourcing’s expected utilities increases first and then decrease.